Peran Motivasi Belajar Siswa dalam Hasil Belajar Tematik pada Sekolah Dasar Negeri Kertosuko 3 Probolinggo, Indonesia: The Role of Student Learning Motivation in Thematic Learning Outcomes at State Elementary School Kertosuko 3 Probolinggo, Indonesia - Ryzca Siti Qomariyah; Mustika Kirana Putri; Irfan Aminullah (Experimental Student Experiences, 2022)
This study aims to analyze the role of student learning motivation on thematic learning outcomes in elementary schools. The research was conducted at SDN Kertosuko 3 with research data obtained from interviews using a quantitative descriptive method. The research was conducted by analyzing interest in learning and student learning outcomes which were calculated based on an authentic assessment system. Based on the results of the analysis conducted in class V SDN Kertosuko 3, it is known that in thematic learning students' motivation can affect learning outcomes. This is evidenced from the results of student learning interest, enjoyment and low student involvement are the keys to creating effective learning in the classroom. Learning must always involve students in it, so that learning is not oriented towards delivering material from the teacher to students. An educator must also be able to think broadly, how learning does not only produce a value at the end of learning. But what is no less important is how the learner can improve the cognitive, affective, and psychomotor aspects of students.